Effect of N-Acetyloxindolylidene-p-chlorophenyl Butenolide on the Corrosion of Copper in Nitric acid Under Annealing Temperature - Khalifa, O.R.; El-Ahmad, E.A.; Misbah, A.A. (Asian Journal of Chemistry, 2010)
The effect of N-acetyloxindolylidene-p-chlorophenyl butenolide as inhibitor on the corrosion behaviour of copper in 2M HNO3 solution has been studied. The weight-loss technique showed that the use of N-acetyloxidolylidene-p-chlorophenyl betenolide affected the corrosion rate of the copper metal. The protection efficiency increases with increasing the substance concentration approaching 82% at 0.01M. In general, the protection efficiency increases with decreasing temperature. Thermometric measurements were carried out in 2M HNO3 in presence and absence of the tested substance. Potential measurements of copper electrode showed that it was shifted to the noble direction with increasing tested substance. Cathodic polarisation was studied on free 2M HNO3 and in presence of different concentrations of the tested substance.